Investigation of genetic diversity in Mycoplasma hyopneumoniae and Mycoplasma hyorhinis - Santos, Lucas Fernando dos (2015)
The two most prevalent Mycoplasmas species present in the swine industry are Mycoplasma hyopneumoniae and Mycoplasma hyorhinis. These pathogens can cause significant economic losses for producers and for the industry. Genetic variability has been observed in M. hyopneumoniae using different techniques and heterogeneity of M. hyorhinis has been the focus of a limited number of studies in the past years. The fact that Mycoplasma genomes contain numerous repetitive regions (VNTR) within their DNA and that they are known to be active sites for genetic recombination has prompted the hypothesis that Multiple locus variable number tandem repeat analysis (MLVA) would be an appropriate technique to investigate genetic variation in Mycoplasma. Therefore, the main goal of this dissertation was to investigate the non random distribution of genotypes from different geographical location using multiple locus variable tandem repeat analysis (MLVA) to type M. hyopneumoniae and M. hyorhinis and advance the knowledge on the genetic diversity and the epidemiology of these pathogens.When the M. hyopneumoniae study was taken in account, a high number of M. hyopneumoniae MLVA types appear to circulate among swine herds with a non-random distribution of the MLVA types among regions, also a common type was not identified among samples obtained from all regions in this study. Likewise, heterogeneity of M. hyorhinis was observed, with limited variation in one of the target VNTR in the M. hyorhinis study. A relevant point observed in this study was that different MLVA types were identified in the same animal in different sample types, which suggests that the pig was colonized with different strains. With a focus on Brazil pig industry, one of the most important in the world, a specific study observed a high heterogeneity of M. hyopneumoniae strains circulating in the country, and the comparison between the number of tandem repeats (TR) in RR1 P97 and RR3 P146 showed a significant negative correlation that may suggest a possible compensatory mechanism that would allow the bacterium to keep its full adhesion capacity even after reduction of TR in RR1-P97. In conclusion, the identification of the genetic heterogeneity of M. hyopneumoniae and M. hyorhinis will assist local epidemiological or outbreak investigations, design future control strategies as well as serve as a potential tool to study the evolutionary biology of this species.